2019
DOI: 10.1111/sji.12737
|View full text |Cite
|
Sign up to set email alerts
|

Chronic granulamatous disease: Two decades of experience from a paediatric immunology unit in a country with high rate of consangineous marriages

Abstract: Chronic granulomatous disease (CGD) is a primary immunodeficiency characterized by susceptibility to bacterial and fungal infections resulting from the inadequacy of phagocytic leucocytes to produce reactive oxygen radicals. CGD is a genetically heterogeneous disease with an X‐linked recessive (XR‐CGD) form caused by mutations in the CYBB (OMIM #300481) gene encoding the gp91(phox) protein, and an autosomal recessive (AR‐CGD) form caused by mutations in the CYBA (OMIM #608508), NCF1 (OMIM #608512), NCF2 (OMIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…These severe general conditions before and at the time of HCT might have been an influence contributing to the poor outcome of non-CYBB CGD patients in the present study. There are also possible differences in the outcomes of HCT for CGD with non-CYBB gene mutations between countries; thus, these mutations are associated with lower incidence of GF and death after HCT in other countries [ Table S2; (4,5,15,17,18)]. It is necessary to evaluate the outcomes of HCT for CGD patients with non-CYBB gene mutations in detail internationally, because of rarity of these gene mutation subtypes of CGD.…”
Section: Discussionmentioning
confidence: 99%
“…These severe general conditions before and at the time of HCT might have been an influence contributing to the poor outcome of non-CYBB CGD patients in the present study. There are also possible differences in the outcomes of HCT for CGD with non-CYBB gene mutations between countries; thus, these mutations are associated with lower incidence of GF and death after HCT in other countries [ Table S2; (4,5,15,17,18)]. It is necessary to evaluate the outcomes of HCT for CGD patients with non-CYBB gene mutations in detail internationally, because of rarity of these gene mutation subtypes of CGD.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Autosomal recessive inheritance is more common in countries with high frequency of consanguinity. [10][11][12] In a Turkish study, 11 consanguinity was reported by 13 of the 24 patients (54%), and 10 out of 13 patients had an autosomal recessive form of the disease. In this cohort, history of consanguinity in the family was reported by only three patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, in Israel, Saudi Arabia, Libya, Oman, Iran, and India, the AR47 0 CGD form prevails (16,24,48,51,59,64,65). However, in Turkey about 30-40% of the CGD patients have X-CGD, but AR47 0 CGD represents about 30-50% of AR-CGD too (19,75,76). We have no clear explanation yet for this discrepancy apart from the appearance of ancestral mutations such as the c.1171_1175delAAGCT mutation in NCF2 in Jordan and close countries and probably the same is true for the c.295_301 delGTGCCCG mutation in CYBA.…”
Section: Discussionmentioning
confidence: 99%